The Effect of Emotional Intelligence, Intellectual Intelligence, and Spiritual Intelligence on Employee Performance through Job Satisfaction as an Intervening Variable (Study on Employees of JNE Malang City) - Amirudin; Pratikto, Heri; Soetjipto, Budi Eko (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to explain the effect of emotional intelligence, intellectual, and spiritual intelligence on employee performance through job satisfaction as an intervening variable (On JNE Employees in Malang City).From the test results obtained the results Emotional Intelligence has a direct and significant effect on Job Satisfaction. Emotional Intelligence has a direct and significant effect on Employee Performance. Intellectual Intelligence has a direct and significant effect on Employee Performance. Spiritual Intelligence has a direct and significant effect on Employee Performance. Emotional Intelligence has an indirect and significant effect on Employee Performance through Job Satisfaction. Intellectual Intelligence has an indirect and significant effect on Employee Performance through Job Satisfaction. Spiritual Intelligence has an indirect and significant effect on Employee Performance through Job Satisfaction.